How fast do Indonesian firms in achieving targeted capital structure? - Faizah Syihab (Al Tijarah, 2018)
Achieving the optimal capital structure are to ensure funds are always available to finance firm’s operations, minimize the cost of capital, to decide on how much to borrow, who or where, when, for how long or in what currency. The mixture of different sources of financing that firm chooses, will affect the value of firms and risk-return to shareholders as debt and equity has its own characteristics. This study expects to give better assessment on how fast is the speed adjustment to achieve the targeted capital structure in Indonesia public listed firm from the period of 2006-2016 using the Generalized Method of Moments (GMM) approach. In this study, the estimated coefficient of the lagged leverage (0.6134) implies that the firm is under-adjust due the coefficient below the target requirement which is less than one and greater than zero. This means that the firms maintain 61.34% of the debt that they have last year and change by 38.66% toward its target leverage. Result depicts that the estimated coefficient of the lagged dependent variables is significant at 1% level. This significant result indicates the existence of target capital structure and firms do make adjustment to long run targets (optimal debt ratio).